REVISANDO LOS TRABAJOS PRÁCTICOS EXPERIMENTALES EN LA ENSEÑANZA UNIVERSITARIA - Lorenzo, María Gabriela (Universidad Nacional del Litoral, 2020)
Teaching Experimental Sciences has always been linked to the development of experimental work. However, when the curricular designs of the courses are considered, the planning and design of practical activities are found not to have received the same attention as other aspects, such as theories or evaluation. Consequently, this article discusses some general characteristics of the practical work in Experimental Science laboratories, while proposing some criteria for their review and analysis. Open practical activities are presented as an alternative to more traditional experimental activities.